Seasonal variation of plasma pepsinogen of sheep in the area of Tricala, Greece - THEODOROPOULOS (Γ. ΘΕΟΔΩΡΟΠΟΥΛΟΣ), G.; KOSTOPOULOS (Ι. ΚΩΣΤΟΠΟΥΛΟΣ), J.; KALOGIANNIS (Δ. ΚΑΛΟΓΙΑΝΝΗΣ), D.; PETRAKOS (Γ. ΠΕΤΡΑΚΟΣ), G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objective of the project was to study the seasonal variation of plasma pepsinogen in sheep during the first year of their life under Greek environmental conditions. Twenty ewes from three flocks in the area of Trikala were used for the study of which seven became pregnant and had lamps. No anthelmintic treatment was applied. Plasma pepsinogen levels were higher (p< 0.001) during spring and summer than winder and autumn. The high pepsinogen levels were attributed to the rainfall and mild temperatures observed in the area of Trikala during winter which created favorable conditions for the development and survival of infective lrvae. No difference was observed between the pepsinogen levels of pregnant and non-pregnant animals. In addition, no correlation between pepsinogen levels and growth rate (GR) of the animals was observed.